Pengaruh Hasil Belajar Matematika Ditinjau Dari Tingkat Motivasi Dan Gaya Belajar Pada Siswa Kelas VIII MTS Muhammadiyah Al Fatah Nangahale - Endah Sari; Wahyuningsih Wahyuningsih; Agnesia Bergita Anomeisa (PT. ALHAFI BERKAH INDONESIA, 2023)
This study aims to find out the comparison of motivation and learning style to the learning outcomes of class VIII MTs Muhammadiyah Al Fatah Nangahale. The population of this study were students of class VIII, totaling 45 students. The sample in the study consisted of 45 students. Data collection was carried out by distributing questionnaires related to motivation and learning styles on mathematics learning outcomes for class VIII MTs Muhammadiyah Al Fatah Nangahale and carrying out documentation to find out students' mathematics learning outcomes. Based on the results of data analysis with a significant level of 5%, it can be concluded: (1) there is an effect of mathematics learning outcomes in terms of learning motivation, (2) there is an effect of mathematics learning outcomes in terms of learning style, (3) there is a significant effect between motivation and learning style on mathematics learning outcomes.